PS-BPC03-3: CARDIOVASCULAR EVENTS PREDICTION RELATED TO GENDER IN PATIENTS WITH HYPERTENSIVE EMERGENCIES IN 12-MONTHS FOLLOW-UP GREEK STUDY. (January 2023) - Fragoulis, Christos; Polyzos, Dimitrios; Dimitriadis, Kyriakos; Konstantinidis, Dimitrios; Mavroudis, Andreas; Leontsinis, Ioannis; Kariori, Maria; Drogkaris, Sotirios; Tatakis, Fotis; Manta, Eleni; Siafi, Eirini; Papakonstantinou, Pantelis; et al.
Abstract : Objective: Currently, epidemiological data on prognosis of patients with hypertensive crises (hC) are limited. The purpose of our study was to register the prevalence and clinical characteristics of patients with hypertensive urgencies (hU) and emergencies (hE) admitting to the emergency department (ED) and during hospitalization and a 12-month follow-up to record new end points in a Greek tertiary hospital. Design and method: The study population included patients reporting to the ED with acute rise in blood pressure (BP) (systolic BP >or = 180mmHg and/or diastolic BP >or = 120mmHg), categorizing as hE and hU depending on the presence or absence of acute hypertension-mediated target organ damage, respectively. In all patients the demographic and clinical information were registered for 12 consecutive months. In addition, there was a 12-month follow-up for new events. Results: Out of 38, 589 patients assessed in the ED during a period of 12 months, 353(0.91%) had HC, out of whom 256(72.5%) had hU and 97(27.5%) had hE. The mean age of the hE patients was 73 ± 12years, 51.5% were males and 86.4% had a history of hypertension. During the study period 3 hE patients did not complete the follow-up. After stratification of hE population by gender, we created two subgroups, males and females, and analyzed the composite end point involving deaths or hospitalizations by cardiovascular causality. Men reported more composite events than women (21 vs 11 events, p = 0.042, hR for males 2.2, 95% CI 1.03–4.6). Cox regression models were adjusted for age, gender, cardiovascular disease, chronic kidney disease and diabetes mellitus. Conclusions: The results indicate male gender as an independent risk factor for deaths or hospitalizations caused by cardiovascular disease in patients with hE. Our registry highlights the commitment for a more intensive follow-up of hE patients, especially for men, and underlines the need for further research in this pathological entity.